Image of the woman of substance in Proverbs 31:10-31 and African context - Nwaoru, Emmanuel O. (Biblische Notizen, 2005)
The history of interpretation of Proverbs 31:10-31 shows that the image of the woman at the centre of the poem is not sacrosanct. Oftentimes, she has been misjud- ged and her activities misunderstood. This paper is an attempt to put in context the image of the אשת־חיל, as she is rightly named (v.10), a woman whose husband, children and general public accord praises for her qualities and activities (vv.28, 31). It also proposes that greater understanding of Prov 31:10-31 lies in discovering the secret of the genre of the text; and that one can find a key to unlock that secret in recital, a genre generally found in African Wisdom corpus, designed to chant the praise of a personality that has achieved greatness in society. Its finding is that Prov 31:10-31 is an ode of an “actual” woman and not a personified mystical figure. Her qualities and activities show her to be an ideal woman and mother, but not idolised or deified. These give her the image of one whose creative force her family and the society at large must acknowledge and appreciate and not a passive victim of social inequalities.